Aortic valve fenestrations: Macroscopic assessment and functional anatomy study. Issue 4 (18th January 2023) - Dudkiewicz, Damian; Zhingre Sanchez, Jorge D.; Hołda, Jakub; Bolechała, Filip; Strona, Marcin; Kopacz, Paweł; Iaizzo, Paul A.; Koziej, Mateusz; Hołda, Mateusz K.; Konieczyńska, Małgorzata
Abstract: Aortic valve fenestrations are defined as a loss of aortic valve leaflet tissue. They are a common but overlooked finding with unclear significance. The aim of this study was to investigate the varied functional anatomies of aortic valve fenestrations. A total of 400 formalin‐fixed autopsied human hearts were macroscopically assessed and the function of the aortic valve of 16 reanimated human hearts were imaged using Visible Heart® methodologies. Aortic valve leaflet fenestrations were present in 43.0% of autopsied hearts (in one leaflet in 24.0%, in two leaflets 16.0%, in all leaflets 3.0%). Fenestrations were mostly present in left (25.5%) followed by right (23.3%) and noncoronary leaflet (16.3%). In 93.8% of cases, the fenestrations form clusters and were mainly located at the free edge of the leaflet in the commissural area (95.4%). Hearts with aortic valve fenestrations had significantly larger aortic valve diameters and aortic valve areas ( p < 0.001). The average surface area sizes of fenestrations were 23.8 ± 16.6 mm 2, and the areas were largest for left followed by right and noncoronary leaflet fenestrations ( p < 0.001). The fenestration areas positively correlated with donor age ( r = 0.31; p = 0.02). Significant hypermobility and subjective weakening of the leaflet adhesion levels of the fenestrated regions were observed. In conclusion, fenestrations of the aortic leaflets are frequent, and their sizes may be significant. They occur in all age groups, yet their size increase with aging. Fragments of leaflets with fenestrations show different behaviors during the cardiac cycle versus unchanged areas.